2020
DOI: 10.1155/2020/2750148
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Most Viewed First 50 Videos on YouTube about Breast Cancer

Abstract: Objective. Breast cancer is the most common cancer type among women worldwide. Today, health consumers search the Internet to gain health information about many diseases including breast cancer. YouTube™ is the second most commonly used website on the Internet. However, the quality and accuracy of health-related YouTube™ videos are controversial. The objective of this study was to investigate the quality and accuracy of breast cancer-related videos on YouTube™. Material and Methods. “Breast cancer” keyword was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 27 publications
4
63
0
2
Order By: Relevance
“…We found that only three of the 50 videos we examined were uploaded by patients and all of these contained misleading content. However, it was also reported that videos uploaded by patients were viewed and liked more than videos uploaded by professionals in some previous studies [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…We found that only three of the 50 videos we examined were uploaded by patients and all of these contained misleading content. However, it was also reported that videos uploaded by patients were viewed and liked more than videos uploaded by professionals in some previous studies [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 95%
“…The reasons for this were that the video content uploaded by health channels and hospital channels was not sufficiently up to date, the information was not given at a sufficient level, the use of medical terms that could not be understood by the viewers, and the promotion of the specific health institution. In the study conducted by Yurdaisik, it was determined that the videos uploaded by health channels were also of medium quality [ 10 ]. Similarly, in the studies conducted by Kuru et al [ 12 ] and Aydin et al [ 11 ], videos uploaded by health channels were reported to be of medium quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, various studies have been carried out to investigate the quality and reliability of video contents related to health issues uploaded to YouTube and whether they are beneficial for patients [ 12 , 13 ]. However, we did not find any study on PC in our literature search.…”
Section: Introductionmentioning
confidence: 99%